2015
DOI: 10.4238/2015.february.13.6
|View full text |Cite
|
Sign up to set email alerts
|

Association between B7-H1 expression and bladder cancer: a meta-analysis

Abstract: ABSTRACT. B7 homolog 1 (B7-H1), which is also known as programmed death-L1, is an important member of the B7/CD28 costimulatory factor superfamily, which are emerging as important mediators of various host immune responses. B7-H1 is differentially expressed in various cell subsets and to different extents in human and murine cells. Human B7-H1 is constitutively expressed at low levels in dendritic cells and activated T cells (compared with high expression in activated murine T cells) and is highly expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previously, two meta-analyses focused on PD-L1 and UC survival were reported. Wu et al [ 34 ] indicated that PD-L1 status was related with worse 3-year overall survival in UC, and Wang et al [ 35 ] revealed that PD-L1 status could predict the clinical stage of UC. Our pooled results with HR value and 95% CI raised a doubt and showed different results with them.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, two meta-analyses focused on PD-L1 and UC survival were reported. Wu et al [ 34 ] indicated that PD-L1 status was related with worse 3-year overall survival in UC, and Wang et al [ 35 ] revealed that PD-L1 status could predict the clinical stage of UC. Our pooled results with HR value and 95% CI raised a doubt and showed different results with them.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Interestingly, patients with superficial BCa showed lower PD-L1 expression than those with invasive BCa. 16 Moreover, blockade of the PD-1/PD-L1 axis was shown to induce a potent antitumor immune response in preclinical mouse models as well as in the clinic. 17,18 Based on the efficacy of Anti-PD-L1 directed therapy, the FDA granted a Breakthrough Therapy Designation for the use of Anti-PD-L1 (MPDL3280A) in metastatic BCa in 2014.…”
Section: Introductionmentioning
confidence: 99%